2016
DOI: 10.1108/ejm-12-2012-0702
|View full text |Cite
|
Sign up to set email alerts
|

The “tug of war” model of foreign product purchases

Abstract: Purpose While globalization has made it easier to consume foreign products, consumption decisions are rarely straightforward. Both love and hate relationships between consumers and countries exist and can even coexist. This paper aims to gain a better understanding of how positive/negative and general/specific consumer attitudes impact foreign product judgment and ownership. An integrative model explores the predictive power of affinity, animosity, cosmopolitanism and ethnocentrism simultaneously. Specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…All scales and subscales were examined for reliability and were found to be reliable (α ≥ .76). Specifically, acculturation was measured with Laroche et al's () 3‐item scale (α Cuba = .84; α Puerto Rico = .85) and included items such as “I consider myself to be American,” and “I feel very attached to all aspects of the American culture.” Ethnic identification was measured by Laroche et al's () 6‐item scale (α Cuba = .86; α Puerto Rico = .91) and included items such as “I consider myself to be Cuban/Puerto Rican,” I would like to be known as Cuban/Puerto Rican,” and “ I am still very attached to the Cuban/Puerto Rican culture.” Identification with the host nation was operationalized by Verlegh's () 4‐item scale (α Cuba = .83; α Puerto Rico = .87) and included items such as “being American means a lot to me” and “when a foreign person praises the US, it feels like a personal complement.” Disidentification with the host nation was measured by Verkuyten and Yildiz's () 5‐item scale (α Cuba = .78; α Puerto Rico = 91) with items such as “I would never say ‘we Americans,’” “I always have the tendency to distance myself from Americans,” and “I never feel addressed when they are saying something about the US and the Americans.” Affinity with the host country was measured by a 14‐item scale (Asseraf & Shoham, ; α Cuba = .86; α Puerto Rico = .93). Items in this scale include statements such as “Americans are friendly people,” “Americans know how to have fun and enjoy their life,” “the landscape in the US is natural,” “the history of the US is very interesting,” and “I know many Americans.” Consumer disidentification was measured by Josiassen's () 6‐item scale (α Cuba = .73; α Puerto Rico = .85) with items such as “in general, I dislike the consumption culture of Americans,” “I object to being seen as just another American,” and “I always tend to not shop in the same places as the Americans.” Product judgments were measured by Shoham et al's () 6‐item scale (α Cuba = .78; α Puerto Rico = .85) with items such as “products made in the U.S.A. are carefully produced and have fine workmanship,” “products made in the U.S.A. show a high degree of technological advancement,” and “products made in the U.S.A. are usually a good value for the money.” Willingness to buy was operationalized with Shoham et al's () 6‐item scale (α Cuba = .61; α Puerto Rico = .74) and included items such as “whenever possible, I avoid buying American products,” “whenever available, I would prefer to buy products made in the U.S.A.,” and “I like the idea of owning American products.” Tables and present the scales' reliabilities for both samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All scales and subscales were examined for reliability and were found to be reliable (α ≥ .76). Specifically, acculturation was measured with Laroche et al's () 3‐item scale (α Cuba = .84; α Puerto Rico = .85) and included items such as “I consider myself to be American,” and “I feel very attached to all aspects of the American culture.” Ethnic identification was measured by Laroche et al's () 6‐item scale (α Cuba = .86; α Puerto Rico = .91) and included items such as “I consider myself to be Cuban/Puerto Rican,” I would like to be known as Cuban/Puerto Rican,” and “ I am still very attached to the Cuban/Puerto Rican culture.” Identification with the host nation was operationalized by Verlegh's () 4‐item scale (α Cuba = .83; α Puerto Rico = .87) and included items such as “being American means a lot to me” and “when a foreign person praises the US, it feels like a personal complement.” Disidentification with the host nation was measured by Verkuyten and Yildiz's () 5‐item scale (α Cuba = .78; α Puerto Rico = 91) with items such as “I would never say ‘we Americans,’” “I always have the tendency to distance myself from Americans,” and “I never feel addressed when they are saying something about the US and the Americans.” Affinity with the host country was measured by a 14‐item scale (Asseraf & Shoham, ; α Cuba = .86; α Puerto Rico = .93). Items in this scale include statements such as “Americans are friendly people,” “Americans know how to have fun and enjoy their life,” “the landscape in the US is natural,” “the history of the US is very interesting,” and “I know many Americans.” Consumer disidentification was measured by Josiassen's () 6‐item scale (α Cuba = .73; α Puerto Rico = .85) with items such as “in general, I dislike the consumption culture of Americans,” “I object to being seen as just another American,” and “I always tend to not shop in the same places as the Americans.” Product judgments were measured by Shoham et al's () 6‐item scale (α Cuba = .78; α Puerto Rico = .85) with items such as “products made in the U.S.A. are carefully produced and have fine workmanship,” “products made in the U.S.A. show a high degree of technological advancement,” and “products made in the U.S.A. are usually a good value for the money.” Willingness to buy was operationalized with Shoham et al's () 6‐item scale (α Cuba = .61; α Puerto Rico = .74) and included items such as “whenever possible, I avoid buying American products,” “whenever available, I would prefer to buy products made in the U.S.A.,” and “I like the idea of owning American products.” Tables and present the scales' reliabilities for both samples.…”
Section: Methodsmentioning
confidence: 99%
“…Disidentification with the host nation was measured byVerkuyten and Yildiz's (2007) 5-item scale (α Cuba = .78; α Puerto Rico = 91) with items such as "I would never say 'we Americans,'" "I always have the tendency to distance myself from Americans," and "I never feel addressed when they are saying something about the US and the Americans." Affinity with the host country was measured by a 14-item scale(Asseraf & Shoham, 2016; α Cuba = .86;α Puerto Rico = .93). Items in this scale include statements such as "Americans are friendly people," "Americans know how to have fun and enjoy their life," "the landscape in the US is natural," "the history of the US is very interesting," and "I know many Americans."…”
mentioning
confidence: 99%
“…In addition to moral obligation, the motivation for the ethnocentric consumers can be purchase of a product to show opposition against another product. Such is the case of Asseraf and Shoham (2016) who argued that the consumers holding negative attitude toward a certain country do not consume products originated from that country. Furthermore, in some cases ethnocentric individuals feel that purchasing imported products would be considered an unpatriotic act (Luque-Martínez et al , 2000; Han, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Research in this area has mainly examined the influence of consumer affinity on the evaluation of products from foreign countries (Asseraf and Shoham 2016;Nes, Yelkur, and Silkoset 2014;Papadopoulos, Banna, and Murphy 2017;Wongtada, Rice, and Bandyopadhyay 2012), and services such as tourism and investment in the focal country (Oberecker and Diamantopoulos 2011). Since past research has generally confirmed that consumer affinity acts as an important predictor of the buying behavior associated with products or services from the affinity country (Papadopoulos, Banna, and Murphy 2017), we propose the following hypothesis.…”
Section: Consumer Affinitymentioning
confidence: 95%
“…Although existing research reveals its favorable influence on product evaluation from the focal country (Asseraf and Shoham 2016;Oberecker and Diamantopoulos 2011;Wongtada, Rice, and Bandyopadhyay 2012), these studies do not necessarily incorporate the factors that promote or inhibit the effect of consumer affinity on foreign product evaluation. This is because studies dealing with consumer affinity have not adopted an experimental approach that is effective in addressing these issues.…”
Section: Introductionmentioning
confidence: 99%